Enhancing problem solving skills through multiliteracies project approach in learning robotics among primary school students - Tan, Ashley Chee Kuang (2021)
In the Malaysian Education Blueprint, one of the students’ aspirations is to develop students’ critical thinking. However, based on the results in the TIMMS and PISA assessment, students have not fully developed this set of skills yet. In addition, students have not fully mastered problem solving skills skills which is vital as it affects employability in the era of the Industrial Revolution 4.0. In this study, 20 level two primary school students in Skudai were selected to participate in this study. They had to undergo as module tailored for this study known as Robotics Project Module. The module consists of 13 sessions including teaching and learning on robotics and programming, completing the tasks given and also a reflection session. Prior to the module, students were administered with a pre-test questionnaire modified from the Problem Solving Rating Scale Employees (PSRS-S) by Lohman (2004) which is a self-assessment and a rater-based assessment to measure problem solving skills among students. Upon completion of the module, pupils were again administered with the same questionnaire as part of post-test. Furthermore, an interview session was also conducted to acquire more information regarding the effects, strength and weaknesses of RPM. The questionnaire was analysed using a paired sample t-test while the interview was analysed using thematic analysis. Through this study, it is evident that RPM do help to enhance students’ problem solving skills in terms of identify the issue, setting goals, generating solutions, making decisions, applying the solution and reflecting. In addition, the module also helped to develop two other skills namely collaborative and communication skills which is part of the aspirations of the Ministry of education Malaysia in developing and preparing students for the real world.